Case 3795: Kryptops palaios Sereno & Brusatte, 2008 (Dinosauria, Abelisauridae): proposed conservation of usage by the designation of a lectotype - Yun, Chan-gyu (Bulletin of Zoological Nomenclature)
Noticed in BZN 76 (30 April 2019): 2. Closed in BZN 76 (30 August 2019): 165.